Influence Of Sonication Assisted Dispersion Method On The Mechanical And Electrical Properties Of Nylon 66/Nano-Copper Nanocomposite - Shueb, Mohammed Iqbal; Abd Manaf, Mohd Edeerozey; Ratnam, Chantara Thevy; Mohamad, Noraiham (Penerbit UTM Press, 2017)

(untitled)
-